Composite adsorption material for efficiently removing U (VI) in nuclear wastewater and preparation method of composite adsorption material

UIO-66-P materials induced by the defects of the same growth in situ in situ in situ in situ, and prepare UIO-66-P@轻 通过 gas gel adsorption materials, solving the existing materials with low uranium adsorption efficiency in low concentration of water solution in low concentrations of water solution The problem has achieved efficient and reusable uranium adsorption effects.

CN119368146APending Publication Date: 2025-01-28Institute of Intelligent Creation, Henan Academy of Sciences +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411527551.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing adsorption materials have low adsorption efficiency in low-concentration aqueous solutions and are difficult to recover, which limits their practical application.

Method used

UIO-66-P materials induced by the defects of the light wood in situ in situ are prepared, and the UIO-66-P@轻 通过 气 suction material is prepared, combining the advantages of biological base materials and MOF composite materials.

Benefits of technology

It significantly improves uranium adsorption efficiency, the maximum adsorption capacity reaches 594mg · G-1, which overcomes the problem of low adsorption efficiency in low concentration environments, and improves the regeneration and stability of the material through structural design.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368146A_ABST
    Figure CN119368146A_ABST
Patent Text Reader

Abstract

The invention provides a composite adsorption material for efficiently removing U (VI) in nuclear wastewater and a preparation method thereof, the composite adsorption material is prepared by growing a defect-induced metal organic framework material UIO-66-P on a low-cost and renewable balsa wood base material in situ to form UIO-66-P at balsa wood composite aerogel, the UIO-66-P is synthesized through defect induction, and the UIO-66-P at the balsa wood composite aerogel is used for adsorbing U (VI) in nuclear wastewater. According to the preparation method, the material hydrophilicity and active adsorption sites are increased, so that the uranium ion adsorption capacity is remarkably improved, the maximum uranium adsorption capacity in a low-concentration aqueous solution can reach 594 mg.g <-1 > which is far better than that of a traditional inorganic material, a carbon-based material and an existing MOF material, and the problem of low adsorption efficiency in a low-concentration environment is successfully solved; the composite material has excellent reproducibility, can still keep efficient uranium adsorption performance after multiple adsorption-desorption cycles, remarkably reduces long-term use cost and waste generation, has wide market application prospects, and provides an efficient solution for sustainable development of nuclear energy industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of nuclear pollutant adsorption, and specifically relates to a composite adsorption material for efficiently removing U(VI) in nuclear waste water and a preparation method thereof. Background Art

[0002] As the global energy shortage and environmental degradation problems intensify, nuclear energy has attracted much attention due to its ability to generate electricity on a large scale and extremely low greenhouse gas emissions. However, the uranium required for nuclear power generation is highly radioactive and toxic. Once it enters the environment, especially the water body, it will cause serious pollution and pose a huge threat to human health. Nuclear wastewater generated during the operation of nuclear power plants and nuclear waste treatment is the main source of pollution. It contains high concentrations of radioactive substances, especially U(VI). If it is not effectively treated and enters the water circulation system, it will have a long-term negative impact on the ecological environment and public health. Therefore, the development of efficient, low-cost and reusable adsorbent materials for recovering uranium from nuclear wastewater is not only crucial to reducing nuclear pollution and ensuring water resource security, but will also promote the sustainable development of nuclear energy and has great environmental and social value.

[0003] In the past few decades, researchers have developed a variety of adsorbent materials for removing uranium from water, including clay minerals, mesoporous silica, layered double hydroxides, metal oxides, activated carbon, graphene oxide, polymer materials, porous organic frameworks and composite materials. However, these adsorbent materials generally have some limitations. For example, inorganic materials and carbon-based materials usually show low uranium adsorption capacity in low-concentration aqueous solutions, and their low mechanical strength or poor recyclability limit their practical applications. In recent years, metal-organic frameworks (MOFs) have attracted widespread attention due to their large surface area, tunable pore structure and functional diversity. For example, Carboni et al. used UiO-68 MOF to adsorb uranium from aqueous solution, and its maximum adsorption capacity reached 217 mg / g (Chem. Sci. 2013, 4(6), 2396-2402). Similarly, Yang et al. studied MOF-76, and under the optimal pH conditions, its uranium adsorption capacity reached 298 mg / g (Chem. Commun. 2013, 49(88),10415-10417). Although MOFs show high adsorption efficiency, their powder form limits their practical recycling and reuse, which has prompted researchers to explore MOF-based composite materials in order to achieve more efficient uranium recovery.

[0004] At the same time, adsorbents based on biomaterials have become one of the hot topics in uranium removal research in recent years due to their advantages such as high specific surface area, permanent porosity and versatility. Lignocellulosic biomass is one of the most abundant natural resources in the world, with an annual output of about 210.7 million tons, containing 30-50% cellulose, 19-45% hemicellulose and 15-35% lignin. Wood is considered a powerful alternative to petroleum-based polymers due to its abundance, environmental friendliness, renewability, biocompatibility and degradability. The unique three-dimensional porous fiber structure of wood makes it particularly suitable for adsorption applications. By removing the lignin-hemicellulose matrix in the wood cell wall, researchers have developed anisotropic wood aerogels with a porosity of up to 95%, demonstrating the potential for directly preparing high-performance aerogel materials from wood.

[0005] The present invention prepares a UIO-66-P@balsa wood composite aerogel adsorption material by in-situ growing defect-induced UIO-66-P material on balsa wood. The composite aerogel exhibits excellent adsorption capacity in the adsorption of U(VI), and the effects of pH value, solution concentration and adsorption time on the adsorption performance are systematically studied. This innovative composite material combines the advantages of bio-based materials and MOF composite materials, providing a promising solution for the efficient recovery of uranium in water. Summary of the invention

[0006] The present invention synthesizes a composite adsorbent material for efficiently removing U(VI) from nuclear wastewater and a preparation method thereof, which solves the technical problems of low adsorption efficiency and difficult recovery of U(VI) by traditional adsorbent materials. The composite adsorbent is prepared by combining the characteristics of lignin cellulose aerogel and MOF with high specific surface area and multiple active sites. The adsorbent exhibits excellent adsorption effect on U(VI).

[0007] In order to achieve the above object, the present invention adopts the following technical scheme: A composite adsorbent material for efficiently removing U(VI) from nuclear wastewater and a preparation method thereof, wherein the first component is a metal organic framework material (UIO-66-P) prepared by defect induction; the ligand is terephthalic acid (BDC); the metal ion is Zr 4+ ; The general formula of metal organic framework can be expressed as: [Zr6(OH)4O4(BDC)6] n -P; component two is specially treated light wood cellulose aerogel; a composite material is prepared using UIO-66-P and light wood cellulose aerogel, wherein the mass proportion of UIO-66-P in the composite material is 10-50%.

[0008] A composite adsorption material for efficiently removing U(VI) from nuclear wastewater and a preparation method thereof, wherein the preparation method is as follows: Step S1: Soaking balsa wood in deionized water for several hours to activate it; placing a certain mass of the activated balsa wood in a mixed solution of NaOH and Na2SO3, and boiling it for several hours to remove lignin and hemicellulose; thoroughly washing the boiled balsa wood with warm water; then boiling the balsa wood in H2O2 (30%) for several hours to further bleach the balsa wood and remove residual lignin and pigment impurities; washing it with deionized water several times, and then freeze-drying the bleached balsa wood to prepare balsa wood cellulose aerogel.

[0009] Step S2: A certain amount of balsa wood cellulose aerogel, ZrCl4 and palmitic acid are dissolved in N,N-dimethylformamide and ultrasonicated for several minutes. Then a certain amount of terephthalic acid is added, and after continued ultrasonication, the mixture is transferred to a Teflon-lined stainless steel autoclave for solvent thermal reaction at a certain temperature. After the reaction is completed, it is naturally cooled to room temperature, and the obtained balsa wood is washed with ethanol several times to remove unreacted ligands and metal salts. In order to maintain its porous structure, the composite material is freeze-dried to obtain UIO-66-P@balsa wood cellulose aerogel composite adsorption material.

[0010] Furthermore, in step S1: the activation soaking time is 1-6h, the mass of the balsa wood is 0.1-0.5g, the concentration of NaOH is 0.5-3M, the concentration of Na2SO3 is 0.2-1M, the volume of the mixed solution is 50-200mL, the boiling time is 6-12h, the volume of H2O2 is 30-100mL, the bleaching time is 1-6h, the washing times are 3-6 times, and the freeze-drying time is 18-30h.

[0011] Furthermore, in step S2: the mass of the balsa wood cellulose aerogel is 0.2-0.5g, the amount of ZrCl4 added is 0.2-1.5g, the amount of palmitic acid added is 1-5g, the amount of terephthalic acid added is 0.1-0.5g, the volume of N,N-dimethylformamide (DMF) is 30-80mL, the ultrasonic time is 10-30min, the reaction temperature is 80-150°C, the reaction time is 12-36h, the washing times are 3-6 times, and the freeze-drying time is 18-30h.

[0012] Compared with the existing method, the present invention has the following beneficial effects: 1. Significantly improve uranium adsorption efficiency, especially in low-concentration environments: The present invention prepares a composite aerogel material with a high synergistic effect by in-situ growing defect-induced UIO-66-P on a balsa wood substrate. UIO-66-P is a metal organic framework (MOF) synthesized by a defect-inducing method. The increase in the number of defects makes the material more hydrophilic and has more active adsorption sites, which can more effectively combine with U(VI) ions. Compared with traditional MOF materials, inorganic adsorbents and carbon-based materials, the uranium adsorption capacity of the material of the present invention is significantly improved, and the maximum adsorption capacity reaches 594 mg·g -1 , far exceeding the existing adsorption materials. This improvement effectively solves the problem of low adsorption efficiency of existing materials in low-concentration uranium wastewater, enabling it to exhibit extremely high adsorption effect in the nuclear wastewater treatment process, further reducing the residual uranium in the water body and reducing the harm to the ecosystem.

[0013] 2. Efficient combination of biomass and MOF, stable structure and excellent mechanical and chemical properties: The composite material organically combines the three-dimensional porous structure of balsa wood with the high specific surface area and adjustable porosity of UIO-66-P. The natural honeycomb structure of balsa wood gives the material excellent support and high porosity, making UIO-66-P evenly distributed in the material, thereby maximizing the exposure of its adsorption sites. The defect induction of UIO-66-P not only increases the number of adsorption sites, but also increases the mass transfer rate of uranium ions in aqueous solution by increasing hydrophilicity. This dual synergistic effect greatly improves the adsorption efficiency of the material. In addition, the composite material has enhanced mechanical strength and chemical stability in structure, overcoming the defects of traditional MOF powder materials that are easy to lose and difficult to recover during operation. Especially in actual industrial application environments, the mechanical toughness of balsa wood enables it to withstand greater pressure and physical damage, while the chemical stability of UIO-66-P enables it to maintain high efficiency under complex water conditions.

[0014] 3. Low cost and renewable In line with the concept of sustainable development, the present invention greatly reduces the manufacturing cost of the adsorption material by selecting balsa wood, a low-cost and renewable biomass material, as the substrate. Balsa wood is abundant in resources, inexpensive, and has excellent biocompatibility and degradability. The use of this material can significantly reduce the risk of environmental pollution during the production and application process. Compared with traditional uranium recovery solutions that rely on petroleum-based materials or expensive adsorbents, the present invention provides a more economical and environmentally friendly solution, which is highly feasible for large-scale industrial applications.

[0015] 3. Excellent regeneration and recycling performance, significantly reducing long-term use costs. The UIO-66-P@balsa wood composite aerogel material of the present invention can still maintain a uranium adsorption capacity close to the original level after multiple adsorption-desorption cycles (at least 6 times), showing excellent regeneration and stability. The adsorption efficiency of traditional adsorption materials usually drops significantly after multiple cycles, resulting in a significant increase in operating costs. However, the defect-induced design of the UIO-66-P material effectively improves its structural stability during the cycle, ensuring that it can still maintain efficient uranium adsorption performance after multiple regeneration cycles. This feature enables the material to effectively reduce the replacement frequency of the adsorption material in long-term use, reduce operating costs and waste generation, and greatly improve economic benefits. At the same time, the excellent regeneration of the material makes it more widely operable in practical applications, suitable for large-scale, continuous industrial wastewater treatment scenarios, showing extremely high market application potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 SEM images of Examples 1-3 and Comparative Example 1; (a) SEM of a cross section of balsa wood; (b) SEM of a longitudinal section of balsa wood; (c) SEM of Example 1, (d) Example 2, and (e) Example 3; Figure 2 XRD patterns of the composite materials prepared in Examples 1-3 and Comparative Example 1; Figure 3 Example 3 Preparation of adsorbents and adsorption effects of U(VI) at different pH values; Figure 4 Adsorption kinetics (a) and adsorption isotherms (b) of the adsorbents prepared in Examples 1-3 and Comparative Example 1; Figure 5 The recycling performance of the catalyst prepared in Example 3. DETAILED DESCRIPTION

[0017] In order to better understand the present invention, the present invention is further described below by way of examples. The examples are only used to explain the present invention and do not constitute any limitation to the present invention.

[0018] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art, and the raw materials used are all commercially available products.

[0019] Balsa wood (Hubei Chemical Fiber Co., Ltd.), ZrCl4, terephthalic acid, palmitic acid, NaOH, Na2SO3 (Shanghai MacLean Biochemical Technology Co., Ltd.), N,N-dimethylformamide (Chengdu Cologne Chemical Co., Ltd.), uranyl nitrate hexahydrate (Hubei Chushengwei Chemical Co., Ltd.); Example

[0020] A composite adsorbent material for efficiently removing U(VI) from nuclear wastewater and a preparation method thereof, comprising the following steps: Step S1: soak 0.3g of balsa wood in deionized water for 2 hours for activation; place a certain mass of the activated balsa wood in 100mL of a mixed solution of 2M NaOH and 0.4M Na2SO3, and boil it for 8 hours to remove lignin and hemicellulose; thoroughly wash the boiled balsa wood with warm water; then place the balsa wood in 50mL of H2O2 (30%) and boil it for 2 hours to further bleach the balsa wood and remove residual lignin and pigment impurities; wash it with deionized water several times, and then freeze-dry it for 24 hours to prepare balsa wood cellulose aerogel.

[0021] Step S2: 0.3 g of balsa cellulose aerogel, 0.4 g of ZrCl4 and 1 g of palmitic acid were dissolved in 50 mL of N,N-dimethylformamide and ultrasonicated for 20 minutes. Then 0.15 g of terephthalic acid was added and ultrasonicated for 20 minutes. Then the mixture was transferred to a Teflon-lined stainless steel autoclave and reacted at 120°C for 24 hours. After the reaction was completed, it was naturally cooled to room temperature. The obtained balsa wood was washed with ethanol 5 times to remove unreacted ligands and metal salts. In order to maintain its porous structure, the composite material was freeze-dried for 24 hours to obtain composite adsorbent 1.

[0022] Example 2 A composite adsorbent material for efficiently removing U(VI) from nuclear wastewater and a preparation method thereof, comprising the following steps: Step S1: same as step S1 in Example 1; Step S2: 0.3 g of balsa cellulose aerogel, 0.8 g of ZrCl4 and 2 g of palmitic acid were dissolved in 50 mL of N,N-dimethylformamide and ultrasonicated for 20 minutes; then 0.3 g of terephthalic acid was added and ultrasonicated for 20 minutes. The mixture was then transferred to a Teflon-lined stainless steel autoclave and reacted at 120°C for 24 hours; after the reaction was completed, it was naturally cooled to room temperature, and the obtained balsa was washed with ethanol 5 times to remove unreacted ligands and metal salts. In order to maintain its porous structure, the composite material was freeze-dried for 24 hours to obtain composite adsorbent 2.

[0023] Example 3 A composite adsorbent material for efficiently removing U(VI) from nuclear wastewater and a preparation method thereof, comprising the following steps: Step S1: same as step S1 in Example 1; Step S2: 0.3 g of balsa cellulose aerogel, 1.2 g of ZrCl4 and 3 g of palmitic acid were dissolved in 50 mL of N,N-dimethylformamide and ultrasonicated for 20 minutes; then 0.45 g of terephthalic acid was added and ultrasonicated for 20 minutes. The mixture was then transferred to a Teflon-lined stainless steel autoclave and reacted at 120°C for 24 hours. After the reaction was completed, it was naturally cooled to room temperature, and the obtained balsa was washed with ethanol 5 times to remove unreacted ligands and metal salts. In order to maintain its porous structure, the composite material was freeze-dried for 24 hours to obtain composite adsorbent 3.

[0024] Comparison 1 A composite adsorbent material for efficiently removing U(VI) from nuclear wastewater and a preparation method thereof, comprising the following steps: 0.3 g of balsa wood was immersed in deionized water for 2 hours for activation; a certain mass of the activated balsa wood was placed in 100 mL of a mixed solution of 2 M NaOH and 0.4 M Na2SO3, and boiled for 8 hours to remove lignin and hemicellulose; the boiled balsa wood was thoroughly washed with warm water; the balsa wood was then placed in 50 mL of H2O2 (30%) and boiled for 2 hours to further bleach the balsa wood and remove residual lignin and pigment impurities; the bleached balsa wood was washed with deionized water several times, and then freeze-dried for 24 hours to prepare Comparative Example 1.

[0025] Performance Testing 1. Adsorption performance. First, a 100 mg / L U(VI) solution was prepared for use. 2 mg of the composite adsorbent material was added to 30 ml of a U(VI) solution having a certain concentration and pH value. The pH value of the solution was adjusted using 0.1 M HCl or NaOH to achieve the desired conditions. The mixture was then continuously oscillated at room temperature to conduct an adsorption experiment.

[0026] The U(VI) concentration was determined by the arsenozo III spectrophotometric method, and the adsorption capacity qe (mg•g -1 ) is calculated as , Among them, C0 (mg•g -1 ) is the initial concentration of U(VI) in the solution, C e (mg•g -1 ) is the equilibrium concentration, V (L) is the volume, and m is the weight of the adsorbent (g).

[0027] 2. Recycling performance. After the adsorption is completed, the composite adsorbent material is desorbed using 20 mL of 0.1 M NaHCO3 solution. The composite material is shaken in the solution for 20 minutes. After desorption, the composite adsorbent material is rinsed with deionized water and reused in subsequent uranium adsorption-desorption cycles. This method can be used to evaluate the reuse rate and efficiency of the composite material in multiple adsorption-desorption cycles.

[0028] Figure 1 Scanning electron microscope (SEM) images of the material are shown; Figure 1 a and 1b clearly show the porous structure and unique channels inside the balsa cellulose aerogel. Figure 1 In c-1e, UIO-66-P nanoparticles are uniformly distributed on the balsa wood surface after in situ production. The UIO-66-P nanoparticles are both attached to the balsa wood surface and firmly embedded in the balsa wood. In addition, when the concentration of the original reaction MOF mother liquor increases, the UIO-66-P nanoparticles on the balsa wood also increase. Scanning electron microscopy verifies the effective synthesis of UIO-66-P@balsa wood composite cellulose aerogel, and the UIO-66-P content in its porous structure is adjustable.

[0029] Figure 2 XRD patterns of the adsorbents prepared in Examples 1-3 and Comparative Example 1; the characteristic peaks of the diffraction peaks of UIO-66-P at 7.4°, 8.5°, 17.1°, 25.7° and 33.1° correspond to the (111), (002), (004), (224) and (137) crystal planes of the material, respectively. At the same time, the main features of the UIO-66-P material at 7.4° and 8.5° have broad peaks, indicating that the crystallinity of the prepared material is reduced. The original balsa wood shows typical cellulose II crystal peaks at 12° and 22.6°. In the composite adsorbent material, both the characteristic peaks of UIO-66-P and the crystallization peaks of cellulose II can be observed, which confirms the successful composite of UIO-66-P nanoparticles and balsa wood.

[0030] Figure 3 The results of the effects of different pH values ​​on uranium adsorption. In the range of pH = 2 to 8, the adsorption capacity of U(VI) of the composite aerogel adsorbent reaches a maximum value of 595 mg•g at a pH value of 4.0. -1, and then gradually decreases with increasing pH. This indicates that pH 4.0 is the optimal value for the adsorption of U (VI), which may be due to favorable electrostatic interactions and the dominance of the most easily adsorbed U (VI) species at this pH. Studies have shown (Environ. Sci.: Nano, 2017, 4(9), 1876-1886.) that with increasing pH, especially when the pH value exceeds 6, the adsorption capacity decreases because U (VI) mostly exists in a negatively charged form, such as UO2(CO3)2 2- or UO2(CO3)3 4- , they are repelled by the electrons of the adsorbent, which reduces the adsorption effect.

[0031] Figure 4 Describes the kinetic and thermodynamic curves of adsorption; e.g. Figure 4 As shown in a, all curves follow a similar trend. Uranium is rapidly adsorbed in the first 50 minutes, and then the adsorption rate slows down until equilibrium is reached. To further explore the adsorption mechanism, a kinetic model is used to fit the adsorption behavior of uranium (VI), and the formula is as follows: Pseudo-first-order: ; Pseudo-second-order: ; Among them, q e (mg•g -1 ) represents the maximum adsorption capacity at equilibrium, q t (mg•g -1 ) represents the adsorption capacity at time t, k (g•mol -1 •min -1 ) represents the kinetic rate constant.

[0032] The fitting results show that the adsorption kinetics of the composite adsorbent conforms to the pseudo-second-order model, indicating that the adsorption process is mainly controlled by chemical adsorption. Figure 4 a shows the data fitted by the pseudo-second-order model, and q calculated by the pseudo-second-order model e The values ​​are very close to the experimental values, which further verifies the applicability of the model. In addition, the results show that the adsorption capacity increases with the increase of UIO-66-P content in the composites, which highlights the key role of UIO-66-P in enhancing uranium adsorption.

[0033] In order to investigate the maximum uranium adsorption capacity of the composite adsorbent, its adsorption isotherm was studied. The experiment was carried out at room temperature, the optimal pH value was 4, the contact time was 5 hours, and the initial uranium concentration ranged from 20 to 200 mg / L; Figure 3As shown, the adsorption capacity of the composite adsorbent increases with the increase of initial uranium concentration; the adsorption equilibrium isotherm of ZIF-8@BS was studied using the Langmuir and Freundlich models; Langmuir model: ; Freundlich model: ; Among them, q m (mg•g -1 ) is the maximum adsorption capacity, q e (mg•g -1 ) is the amount of uranium adsorbed at equilibrium, C e is the equilibrium concentration (mg•L -1 ), K L is the Langmuir constant, K F is the Freundlich constant and n is the Freundlich index.

[0034] The results show that the adsorption equilibrium isotherm of the composite adsorbent is more consistent with the Langmuir model, indicating that the adsorption process is a single-layer chemical adsorption. According to the Langmuir model, the theoretical maximum adsorption capacity of the composite adsorbent is basically consistent with the theoretical maximum adsorption capacity of adsorption kinetics. This further confirms the effectiveness and reliability of the composite adsorbent as a high-efficiency uranium adsorbent.

[0035]

[0036] Figure 5 In order to test the recyclability of the adsorbent, the adsorbent obtained in Example 3 was used to carry out a recyclability experiment of 6 adsorption-desorption cycles. Before each cycle, the adsorbent was desorbed using 0.1 M NaHCO3 solution and then freeze-dried. After 6 cycles, the adsorbent still maintained a high adsorption capacity, showing excellent durability and reusability, which is crucial to reducing the cost of uranium recovery in practical applications.

[0037] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

[0038] The basic principles and main features of the present invention and the advantages of the present invention are shown and described above. For those skilled in the art, it is obvious that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention; therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is limited by the attached claims rather than the above description. Therefore, it is intended to include all changes within the meaning and scope of the equivalent elements of the claims in the present invention, and any figure marks in the claims should not be regarded as limiting the claims involved.

[0039] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A composite adsorbent material for efficiently removing U(VI) from nuclear wastewater and a preparation method thereof, characterized in that: Component 1 is a metal organic framework material (UIO-66-P) prepared by defect induction; the ligand is terephthalic acid (BDC); the metal ion is Zr 4+ ; The general formula of metal organic framework can be expressed as: [Zr6(OH)4O4(BDC)6] n ; Component two is specially treated light wood cellulose aerogel; a composite material is prepared using UIO-66-P and light wood cellulose aerogel, wherein the mass proportion of UIO-66-P in the composite material is 10-50%.

2. A composite adsorbent material for efficiently removing U(VI) from nuclear waste water according to claim 1 and a preparation method thereof, wherein the preparation method is as follows: Step S1: immersing balsa wood in deionized water for several hours to activate it; placing a certain mass of the activated balsa wood in a mixed solution of NaOH and Na2SO3, and boiling it for several hours to remove lignin and hemicellulose; thoroughly washing the boiled balsa wood with warm water; then boiling the balsa wood in H2O2 (30%) for several hours to further bleach the balsa wood and remove residual lignin and pigment impurities; washing it with deionized water several times, and then freeze-drying the bleached balsa wood to prepare balsa cellulose aerogel; Step S2: A certain amount of balsa wood cellulose aerogel, ZrCl4 and palmitic acid are dissolved in N,N-dimethylformamide and ultrasonicated for several minutes, then a certain amount of terephthalic acid is added, and after further ultrasonication, the mixture is transferred to a Teflon-lined stainless steel autoclave for solvent thermal reaction at a certain temperature. After the reaction is completed, it is naturally cooled to room temperature, and the obtained balsa wood is washed with ethanol several times to remove unreacted ligands and metal salts. In order to maintain its porous structure, the composite material is then freeze-dried to obtain UIO-66-P@balsa wood cellulose aerogel composite adsorption material.

3. A composite adsorbent material for efficiently removing U(VI) from wastewater and a preparation method thereof as claimed in claim 2, characterized in that: In step S1: the activation soaking time is 1-6h, the mass of the balsa wood is 0.1-0.5g, the concentration of NaOH is 0.5-3M, the concentration of Na2SO3 is 0.2-1M, the volume of the mixed solution is 50-200mL, the boiling time is 6-12h, the volume of H2O2 is 30-100mL, the bleaching time is 1-6h, the washing times are 3-6 times, and the freeze-drying time is 18-30h.

4. A composite adsorbent material for efficiently removing U(VI) from wastewater and a preparation method thereof as claimed in claim 2, characterized in that: In step S2: the mass of the balsa wood cellulose aerogel is 0.2-0.5g, the amount of ZrCl4 added is 0.2-1.5g, the amount of palmitic acid added is 1-5g, the amount of terephthalic acid added is 0.1-0.5g, the volume of N,N-dimethylformamide (DMF) is 30-80mL, the reaction temperature is 80-150°C, the reaction time is 12-36h, the number of washing times is 3-6 times, and the freeze-drying time is 18-30h.

5. The method for preparing a composite material according to claim 2, characterized in that: The UIO-66-P content of the UIO-66-P@light wood cellulose aerogel composite adsorption material is 10-50%.

6. The method for preparing a composite material according to claim 2, characterized in that: The UIO-66-P is a metal organic framework prepared by defect induction, and the increase in the number of defects will cause the MOF structure to have stronger hydrophilicity.

7. The composite material according to claim 2, characterized in that The composite material is used for efficiently removing U(VI) from aqueous solution.

8. A composite adsorbent material for efficiently removing U(VI) from nuclear wastewater prepared by the preparation method according to claims 1-6.